2013
DOI: 10.1523/jneurosci.2383-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Raphe GABAergic Neurons Mediate the Acquisition of Avoidance after Social Defeat

Abstract: Serotonin (5-HT) modulates neural responses to socioaffective cues and can bias approach or avoidance behavioral decisions, yet the cellular mechanisms underlying its contribution to the regulation of social experiences remain poorly understood. We hypothesized that GABAergic neurons in the dorsal raphe nucleus (DRN) may participate in socioaffective regulation by controlling serotonergic tone during social interaction. We tested this hypothesis using whole-cell recording techniques in genetically identified D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
172
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(190 citation statements)
references
References 66 publications
15
172
2
1
Order By: Relevance
“…Manipulations evoking hypo-5-HTergic states such as tryptophan depletion exert prodepressive effects (Blokland et al, 2002;Feder et al, 2011), whereas selective 5-HT reuptake inhibitors (SSRIs) that block the 5-HTT and hence enhance synaptic 5-HT levels have antidepressant and anxiolytic efficacy (Fuller and Wong, 1990). Preclinical research mirrors this relationship, as reduced firing of 5-HTergic neurons is often observed in animal models of depression and anxiety (Bambico et al, 2009;Challis et al, 2013). Although genome-wide association studies (GWAS) have thus far not identified genetic risk loci for depression (Flint and Kendler, 2014), the relationship between perturbed 5-HTergic signaling and affective behavior is further supported by genetic linkage and association studies.…”
Section: -Ht and Emotional And Cognitive Behaviormentioning
confidence: 99%
“…Manipulations evoking hypo-5-HTergic states such as tryptophan depletion exert prodepressive effects (Blokland et al, 2002;Feder et al, 2011), whereas selective 5-HT reuptake inhibitors (SSRIs) that block the 5-HTT and hence enhance synaptic 5-HT levels have antidepressant and anxiolytic efficacy (Fuller and Wong, 1990). Preclinical research mirrors this relationship, as reduced firing of 5-HTergic neurons is often observed in animal models of depression and anxiety (Bambico et al, 2009;Challis et al, 2013). Although genome-wide association studies (GWAS) have thus far not identified genetic risk loci for depression (Flint and Kendler, 2014), the relationship between perturbed 5-HTergic signaling and affective behavior is further supported by genetic linkage and association studies.…”
Section: -Ht and Emotional And Cognitive Behaviormentioning
confidence: 99%
“…First, activation of DRN neurons strongly drives reward behaviors primarily in a glutamate-dependent manner. Optogenetic suppression of DRN GABA neuron activity disinhibits non-GABA neurons and prevents mice from acquiring social avoidance (Challis et al 2013), which gives the initial hint that the activity of DRN non-GABA neurons may reduce the aversiveness of social defeat. Our group examined the behavioral effects of optogenetic stimulation of mouse DRN Pet-1 neurons (Liu et al 2014), which consist of mostly 5-HT neurons ( 90%) and some purely glutamate neurons ( 10%).…”
Section: Optogenetics Reveal Two Different Roles Of Drn Neurons In Rementioning
confidence: 99%
“…These two neuronal types, which most likely represent GABAergic and 5-HT neurons, were identified by their cell type-specific firing pattern and firing frequencies (9,10). responses in HEK cells transiently expressing vMo, supplemented with 10 μM 9-cis retinal (white circles; n = 6), all-trans retinal (black triangles; n = 6) and without supplementation (black circles; n = 6) after repeated light stimulation (2-s light pulse, 1-s delay, 60 repeats), with HEK cells transfected with mCherry as control (white diamonds; n = 6); and (C) heterologous expression of vMo-CT 5-HT2c C-terminally tagged with mCherry fused to the C-terminal domain of the human 5-HT 2c -R in HEK cells and Ca 2+ responses in HEK cells transiently expressing vMo-CT 5-HT2c , supplemented with 10 μM 9-cis retinal (white circles; n = 6), all-trans retinal (black triangles; n = 6) and without any supplements (black circles; n = 6) after repeated light stimulation (2-s light pulse, 1-s delay, 60 repeats; 485 nm) with HEK cells transfected with mCherry (white diamonds; n = 6) as a control.…”
Section: -Ht 2c -Rs Are Located On Gabaergic Neurons In the Drn Andmentioning
confidence: 99%